Uczynić widocznym niewidoczne w krajobrazie (polikryzysu). O projektach artystycznych Richarda Mosse’a, Nicolasa Gouraulta i Jeremy’ego Kamala - Marcela, Mikołaj (Przestrzenie Teorii, 2025)
Although the artistic projects of Richard Mosse (Broken Spectre), Nicolas Gourault (Unknown Label) and Jeremy Kamal (Mojo: Da Floods) differ in form and subject matter, they all focus on the variously understood landscape and the complex network of relations between humans, nature and new technologies that emerges in it. These projects make visible what usually remains invisible, especially in the context of the sources of what we have recently called the polycrisis. They are also proof that contemporary art, through the use of new technologies, is able to confront us in an innovative way with the grim realities of the Anthropocene and Mortonian hyperobjects such as global warming, artificial intelligence and Western colonialism.